Kinaesthetic imagery ability moderates the effect of an AO+MI intervention on golf putt performance: A pilot study - McNeill, E.; Ramsbottom, N.; Toth, A.; Campbell, M. J. (Psychology of Sport and Exercise, 2020)
Previous research has established that motor imagery (MI) and action observation (AO) independently enhance the performance and learning of motor skills. Recent studies have demonstrated that combining AO and MI (AO + MI) elicits increased activity in motor regions of the brain and enhances performance more than either AO or MI alone. Kinesthetic imagery (KI) ability refers to the ease with which one can sense their own body and imagine how a movement feels during a task (Malouin et al., 2007). KI ability may be of particular importance when engaging with AO + MI as the provision of an external visual stimulus through AO renders the visual component of MI redundant. The current study aims to add to the emerging body of behavioural evidence demonstrating the performance benefits of AO + MI by exploring the effect of an AO + MI intervention on golf putting performance, as well as exploring the role that KI ability represents in AO + MI effectiveness. Method: Right-handed male golfers (N = 44) of varying skill level performed twenty 15-foot putts before and after a 3.5 min AO + MI intervention (AO + MI group; mean handicap = 7.5, SD = 4.3) or a similarly timed passive reading task (Control group; mean handicap = 11.5, SD = 5.4). Using the MIQ-3 questionnaire, participants in both experimental groups were classified according to kinesthetic imagery ability where: a mean score =6 were classified as good imagers. Performance accuracy was measured using mean radial error (MRE), precision was quantified via bivariate error (BVE) and putter kinematics were recorded by SAM Puttlab. Results: Results from a series of ANCOVAs indicate that good kinesthetic imagers who received the AO + MI intervention were significantly more precise (BVRE) on the putting task than good kinesthetic imagers in the Control group (p = 0.041, d = 0.678). Good kinesthetic imagers in the intervention group also significantly outperformed good kinesthetic imagers in the control group on a measure of speed control (SD of error scores along the axis of progression) in golf putting (p = 0.041). Conclusions: Our results suggest that the presence of AO with MI increases the relevance of kinesthetic cues, that good kinesthetic imagers are able to utilise for subsequent performance benefits during the putting task. We discuss the increased importance of kinesthetic awareness/feel following the intervention as an explanation for such improvements in performance.